Solon Hannibal Borglum papers - Borglum, Solon Hannibal, 1868-1922.
Correspondence, articles, commission files, subject files, biographical material, printed matter, scrapbook, photographs, and other papers relating chiefly to Borglum's career as a sculptor and to his works of art. Documents his activities with the Silvermine Group of Artists, New Canaan, Conn.; and the School of American Sculpture, New York, N.Y. Also documents Borglum's World War I service in France with the Young Men's Christian Association, Les Foyers du Soldat, and the American Expeditionary Force Art Training Center. Includes material pertaining to the time he and his wife spent at the Crow Creek Indian Reservation, S.D., in 1899. Also includes drawings and watercolors created by Native American schoolchildren attending the Fort Spokane Boarding School, Miles, Wash. Correspondents include Theodore Roosevelt, Augustus Saint-Gaudens, Booker T. Washington, Leonard Wood, and Borglum's wife, Emma Vignal Borglum, and daughter, Monica Borglum Davies.
Microfilm edition of clippings and magazine articles available
Microfilm of originals in private hands.
Private
Library of Congress Prints and Photographs Division.
Sculptor.
Collection material in English, with French.
Keywords: Borglum, Emma Vignal, -- 1864-1934 -- Correspondence; Davies, Monica Borglum, -- 1903-1997 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Saint-Gaudens, Augustus, -- 1848-1907 -- Correspondence; Washington, Booker T., -- 1856-1915 -- Correspondence; Wood, Leonard, -- 1860-1927 -- Correspondence; United States. -- Army. -- American Expeditionary Forces. -- Art Training Center; Fort Spokane Boarding School; Les Foyers du Soldat; School of American Sculpture; Silvermine Group of Artists; Art -- Study and teaching -- France; Art -- Study and teaching -- New York (State) -- New York; Artist colonies -- Connecticut -- New Canaan; Artists -- Connecticut -- New Canaan; Children's art; Indians of North America -- Washington (State); Sculpture, American; World War, 1914-1918 -- Art and the war; World War, 1914-1918 -- War work -- Young Men's Christian associations; World War, 1914-1918 -- War work -- France; Sculptors -- United States; Sculptors